The chemistry of Formycin biosynthesis - Richards, Nigel G. J.; Naismith, James H. (Frontiers in Chemical Biology, 2024)
Remarkable progress has been made to elucidate the structural and mechanistic enzymology of the biosynthetic pathways that give rise to naturally occurring C-nucleosides. These compounds are generally cytotoxic and exhibit interesting antiviral, antibiotic and anti-parasitic activity. Here we review current knowledge concerning formycin biosynthesis and highlight deficiencies in our understanding of key chemical transformations in the pathway.